Acoustics basic physics, theory, and methods - Filippi, P.; Filippi, Paul (Academic Press, 1999)
The book is devoted to the very basis of acoustics and vibro-acoustics. The physics of the phenomena, the analytical methods and the modern numerical techniques are presented in a concise form. Many examples illustrate the fundamental problems and predictions (analytic or numerical) and are often compared to experiments. Some emphasis is put on the mathematical tools required by rigorous theory and reliable prediction methods. Key Features * a series of practical problems, which reflect the content of each chapter * reference to the major treatises and fundamental recent papers * current computing techniques, used in problem solving.